Peran Dukungan Sosial Terhadap Kualitas Hidup Pada Orang Dengan HIV/AIDS (ODHA) : Literatur Review - Fatimatuz Zuhroh; Abdul Muhid (UNS Press, 2022)
The number of cases of HIV/AIDS is increasing every year. In Indonesia, cases of HIV/AIDS announced in May 2021 reached 558,618 cases, making it an important matter to pay attention to. Damage that occurs to the organs of a person affected by HIV-AIDS will make that person susceptible to various deadly diseases. A person living with HIV/AIDS will feel hopeless, frustrated, and sad. In addition, the existence of a sense of shame and separation in the community resulted in a decrease in the quality of life of PLWHA. So, it is very important to strive for quality of life in individuals infected with HIV/AIDS by providing enthusiasm, and motivation. Therefore, this paper was made entirely to determine the role of social support with quality of life in individuals with HIV/AIDS. The writing of this article uses the literature review method with reference sources from journals or articles obtained from google scholar and researchgate.net. The results of research from this literature, which show that social support and quality of life are interrelated.